2015 American Control Conference (ACC) 2015
DOI: 10.1109/acc.2015.7170826
|View full text |Cite
|
Sign up to set email alerts
|

An approximate solution to the optimal coordination problem for autonomous vehicles at intersections

Abstract: Abstract-In this paper, we address the problem of optimal and safe coordination of autonomous vehicles through a traffic intersection. We state the problem as a finite time, constrained optimal control problem, a combinatorial optimization problem that is difficult to solve in real-time. A low complexity computational scheme is proposed, based on a hierarchical decomposition of the original optimal control formulation, where a central coordination problem is solved together with a number of local optimal contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 64 publications
(46 citation statements)
references
References 10 publications
0
46
0
Order By: Relevance
“…In [8] it was shown that the function Φ i (t) has a single unique minimum, but that it is not convex in general. We show here that Φ i (t i ) is C 0 , and piece-wise…”
Section: Properties Of Problem (12)mentioning
confidence: 99%
See 4 more Smart Citations
“…In [8] it was shown that the function Φ i (t) has a single unique minimum, but that it is not convex in general. We show here that Φ i (t i ) is C 0 , and piece-wise…”
Section: Properties Of Problem (12)mentioning
confidence: 99%
“…To reduce the computational requirements of solving the coordination problem (11) with long horizons and large state spaces, a two-level decomposition of Problem (12) was presented in [8]. In this decomposition, the top level consists of a time-slot allocation problem and the low level consists of one optimal control problem for each of the M vehicles.…”
Section: Decompositionmentioning
confidence: 99%
See 3 more Smart Citations